Enzymatic Fuel Cells Solely Supplied with Unpurified Cellobiose Dehydrogenase and Laccase in Microorganism's Culture Supernatants. Issue 11 (24th October 2014) - Sané, Sabine; Heilemann, Corinna; Salavei, Pavel; Rubenwolf, Stefanie; Jolivalt, Claude; Madzak, Catherine; Zengerle, Roland; Nielsen, Peter J.; Kerzenmacher, Sven
Abstract Enzymatic electrodes have great potential for catalysing the direct conversion of chemical compounds into electricity with the use of redox enzymes. However, expensive and time‐consuming enzyme purification and the frequent need to add mediators are considered as drawbacks of enzymatic electrodes. We report a biofuel cell at pH 5, supplied with the unpurified enzymes laccase and cellobiose dehydrogenase (CDH) in crude culture supernatant, without the further addition of mediators. A maximum power output of 6.2±1.2 μW cm−2 was achieved by using supernatants containing laccase from Trametes versicolor (2.84 UmL−1) and CDH (0.90 UmL−1) from a recombinant yeast Yarrowia lipolytica YPC4. In comparison, the supply of purified enzymes (laccase: 2.40 UmL−1, CDH: 0.15 UmL−1) in a buffer solution yielded only about a twofold higher power density. Our results demonstrate the feasibility of using unpurified laccase and CDH in an enzymatic biofuel cell, which can simplify its construction and operation.